BUZZ GROUP DALAM MENINGKATKAN PERILAKU PEMBERIAN MP-ASI - Ruri Noor Aini; Yuni Sufyanti Arief; Ni Ketut Alit (Pediomaternal Nursing Journal, 2014)
Children aged 6-24 months is a very important to growing up. If the children doesn’t obtain nutrional food as needed, then their golden period turning into critical period of growth now or later. The aim of this study was to identify and analyze the effects of using buzz group as a media to change mother’ behavior in giving complementary food to children aged 6-24 months. This study was using a pre-experiment design with a pre and post test. Its population were mothers who have children aged 6-24 months at Baby Health Centre of Kapasari Village. The sample were choosed through purposive sampling technique based on inclution and exclution criteria. The independent variable was buzz group, the dependant variable was mother’s behaviour. Data were collected by questionnaire that analyzed using Wilcoxon Signed Rank Test with alpha level ≤0,05 as a signification. The result of Wilcoxon Signed Rank Test showed that this method affected the change in knowledge (p=0,004), attitude (p=0,034) and the actions (p=0,005). Health education with buzz group as a method has influence on the mother’s behaviour in giving complementary feeding at Baby Health Center of Kapasari village and it can be used as a media by nurses to improve the mother's behavior in the provision of complementary feeding in children aged 6-24 months. Further researcher is expected to have a longer research time to improve the quality of observing the mother's action in giving complementary feeding in children aged 6-24 months